2017
DOI: 10.3945/jn.116.240473
|View full text |Cite
|
Sign up to set email alerts
|

Whey Protein Supplementation and Higher Total Protein Intake Do Not Influence Bone Quantity in Overweight and Obese Adults Following a 36-Week Exercise and Diet Intervention

Abstract: Background: Controversy exists concerning the effects of higher total protein intake (TPro) on bone health, which may be

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 76 publications
2
9
0
Order By: Relevance
“…Recently, it was shown that 23 of 24 dietary supplements available in fitness equipment and online shops contained anabolic steroids 2. However, these supposedly pro-androgenic supplements presumably differ from the more commonly used whey and soy protein supplements 34. Notwithstanding, both products are listed as dietary supplements rather than medical drugs; thus, they are not rigorously tested,5 do not necessarily list all contents,2 and consequently might contain known and unknown active components 36…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was shown that 23 of 24 dietary supplements available in fitness equipment and online shops contained anabolic steroids 2. However, these supposedly pro-androgenic supplements presumably differ from the more commonly used whey and soy protein supplements 34. Notwithstanding, both products are listed as dietary supplements rather than medical drugs; thus, they are not rigorously tested,5 do not necessarily list all contents,2 and consequently might contain known and unknown active components 36…”
mentioning
confidence: 99%
“…We attempted to identify similar studies using literature search in electronic databases (PubMed, EMBASE, MedlinePlus, Ovid MEDLINE, and Scopus) from their inception to October 2017, albeit we failed to identify any previous publications on this matter. Based on the known product declaration of the protein supplements used by the men in the present pilot study, it predominantly consisted of whey, which is one of the two generally used protein dietary supplements – the other being soy 34. Previous studies investigated the potential impact of soy supplements on sex hormone levels whereas the evidence for whey products are scarce.…”
mentioning
confidence: 99%
“…Wright et al . ( 30 ) did not find an influence of 9-month whey protein supplementation on bone quantity (bone mineral density or content) in overweight and obese adults.…”
Section: Resultsmentioning
confidence: 91%
“…Whey protein isolate and a free amino acid mixture simulating the amino acid composition of the whey protein isolate had a similar effect on satiety of normal-weight women as presented by Chungchunlam et al (29) . Wright et al (30) did not find an influence of 9-month whey protein supplementation on bone quantity (bone mineral density or content) in overweight and obese adults.…”
Section: Resultsmentioning
confidence: 93%
“…However, the effects of animal protein during weight loss on (markers of) bone health remains poorly studied. One double-blind, randomised, placebo-controlled trial addressed this via whey protein supplementation (20 and ≥40 g) during a combined resistance and aerobic exercise training program in obese/overweight adults [92]. In this study, whey protein, regardless of dose, had no effect on BMD or bone mineral content (BMC) during the intervention.…”
Section: Bonementioning
confidence: 90%